Complete and partial XYLT1 deletion in a patient with neonatal short limb skeletal dysplasia. Issue 2 (24th November 2015) - van Koningsbruggen, Silvana; Knoester, Hennie; Bakx, Roel; Mook, Olaf; Knegt, Lia; Cobben, Jan Maarten
Abstract : We report on a boy with a neonatal short limb skeletal dysplasia with serious medical complications, associated with one intragenic and one complete deletion of XYLT1 . XYLT1 mutations have recently been reported as causative in recessive Desbuquois skeletal dysplasia (DBSD), but the skeletal features in our patient do not fit this diagnosis. It is possible that the phenotype of XYLT1 mutations extends to more aspecific types of short limb skeletal dysplasias and not to DBSD alone. © 2015 Wiley Periodicals, Inc.